Proposta de um sistema de gestão de resíduos de serviços de saúde para os cursos da área da saúde numa universidade comunitária - Müller, Adriani Maria (2010)
This study aimed to propose a management system of Health Services Waste HSW for courses in the health area in a community university, based on leading provided by the Brazilian legislation linked to the health sector, the Environmental Management System, established by ISO 14001, and the research results from the application of two questionnaires: one for data collection of students and one for teachers and employees. The research was exploratory-descriptive, and used integration approaches between qualitative and quantitative analysis. It was found that the legislation on health services waste is unknown by 94% of students and 82% of teachers and employees do not know the destination of such waste. Other research results obtained in practical classes and services to the community demonstrated the need for more comprehensive and consistent information about the HSW. The knowledge of students, teachers and employees is directed and specific to each situation, but with a gap in relation to the legislation and management of HSW. It was proposed a Management model of Health Services Waste which is obtained in teaching activities that become a set of actions aiming to the quality and efficiency of academic practices, and emphasizing environmental education.